Ventilatory, metabolic, and thermal responses to hypercapnia in female rats: effects of estrous cycle, ovariectomy, and hormonal replacement - Marques, Danuzia A. [UNESP]; Carvalho, Debora de; Silva, Glauber S. F. da [UNESP]; Szawka, Raphael E.; Anselmo-Franci, Janete A.; Bicego, Kenia C. [UNESP]; Gargaglioni, Luciane H. [UNESP] (Amer Physiological Soc, 2015)
The aim of this study was to examine how estrous cycle, ovariectomy, and hormonal replacement affect the respiratory [ventilation ((V)over dotE), tidal volume, and respiratory frequency], metabolic ((V)over dotO(2)), and thermoregulatory (body temperature) responses to hypercapnia (7% CO2) in female Wistar rats. The parameters were measured in rats during different phases of the estrous cycle, and also in ovariectomized (OVX) rats supplemented with 17 beta-estradiol (OVX + E-2), with a combination of E-2 and progesterone (OVX + E2P), or with corn oil (OVX + O, vehicle). All experiments were conducted on day 8 after ovariectomy. The intact animals did not present alterations during normocapnia or under hypercapnia in (V)over dotE, tidal volume, respiratory frequency, (V)over dotO(2), and (V)over dotE/(V)over dotO(2) in the different phases of the estrous cycle. However, body temperature was higher in female rats on estrus. Hormonal replacement did not change the ventilatory, thermoregulatory, or metabolic parameters during hypercapnia, compared with the OVX animals. Nevertheless, OVX + E-2, OVX + E2P, and OVX + O presented lower hypercapnic ventilatory responses compared with intact females on the day of estrus. Also, rats in estrus showed higher (V)over dotE and (V)over dotE/(V)over dotO(2) during hypercapnia than OVX animals. The data suggest that other gonadal factors, besides E-2 and P, are possibly involved in these responses.
Keywords: CO2; estrogen; progesterone; cycling rats; breathing